Tracheal adenoid cystic carcinoma presenting as a locally advanced thyroid gland carcinoma - Mariam Ben Ayed, MD; Makram Tbini, MD; Inès Riahi, MD; Sarra Idriss, MD; Mamia Ben Salah, MD (Radiology Case Reports)
Tracheal adenoid cystic carcinoma is a rare malignancy. We report the case of a 65-year-old male who presented to our department due to a 3-month history of mild dysphagia without other associated symptoms. The neck, laryngeal, and hypopharyngeal examinations were normal. Ultrasound showed hypertrophy and marked hypoechogenicity of the left thyroid lobe without suspicious nodules. Fine needle aspiration of the hypoechogenic area revealed an adenoid cystic carcinoma. A tracheal origin was then suspected and it was confirmed by a flexible bronchoscopy that showed a tumor located in the proximal tracheal reducing its lumen by 50%. The biopsy confirmed the diagnosis of tracheal adenoid cystic carcinoma. We performed a computed tomography scan showing a mass at the angle between the trachea and esophagus infiltrating the left thyroid gland. Magnetic resonance imaging confirmed the tumor's important local and regionregional extension at the thyroid gland, esophagus, larynx, and mediastinum. The tumor was judged as unresectable and the patient received radiotherapy and an endotracheal sent. After a follow-up period of 2 years, the tumor remained stable, and the patient receivedThis study aims to determine the clinical, radiological, and therapeutic aspects of advanced adenoid cystic carcinoma.